The Influence of Social Media and Equity on the Loyalty of Generation Z Shopee Users in Tangerang City - Rusbiansyah Perdana Kusuma; Agus Suherman; Rida Ristiyana; Regita Putri Infantri (International Journal of Management Science, 2023)
Generation Z is a generation that is proficient and knowledgeable about the internet and is accustomed to information and digital applications. This research aims to determine the influence of social media and equity on the loyalty of Generation Z Shopee users in Tangerang City. This study employs an explanatory quantitative method and utilizes an empirical research model, collecting data through an online questionnaire with 124 respondents. The research findings indicate that social media does not have a significant influence on Shopee user loyalty, as evidenced by the original sample size. On the other hand, equity factors such as brand trust, brand awareness, and perceived value significantly influence Shopee user loyalty, as demonstrated by the original sample size. The results of this study can contribute to enhancing the quality of Shopee and its marketing through social media to make it more effective in attracting and retaining users' loyalty.